PENINGKATAN KINERJA GURU DALAM PENGEMBANGAN EVALUASI HASIL BELAJAR MELALUI SUPERVISI AKADEMIS KEPALA SEKOLAH DI UPT SDN GEMBOR 2 - Dimyati, Yayat (STAI Darul Qalam Tangerang, 2022)
The feasibility of teaching is not enough to only be measured based on formal education but must also be measured based on the teacher's ability to teach and mastery of the material, master, choose and use methods, media and evaluation of learning. The ability of elementary school teachers in mastering learning materials is generally very worrying because of the sample of elementary school teachers who were asked to show their ability to master lesson materials, 70% did not master the subject matter, while only 30% mastered the subject matter. Such conditions are exacerbated by the less than optimal supervisory function of the Principal. If so far many opinions state that the professionalism of teachers in Indonesia is relatively low or inadequate, this is a result of the lack of supervision of the principal. The purpose of this school action research (PTS) is to find out the extent to which the principal's coaching through academic supervision is to improve teacher performance in the development of evaluation of learning outcomes. In this school action research (PTS) it was carried out in 3 cycles, from the results of the actions taken it was proven to be able to improve teacher performance by achieving ideal standards. From 60.45% in the first cycle, it can increase to 70.45% in the second cycle, and 77.27% in the third cycle. The results of this action research indicate that coaching through the academic supervision of the principal can improve teacher performance in the development of evaluation of learning outcomes with completeness reaching 100%.